Constituent power: a genealogy - Lindsay, Adam (2017)
That ‘the people’ is a representative claim is accepted by many democratic theorists. Many of these same theorists take constituent power to be the capacity of the rightful bearers of this title to express this claim and found a constitution. Accordingly, constituent power is understood as the ‘other’ of constituted power, a radical and self-legitimating collective will that is outside or beyond the law. Some suggest that this relationship is ‘paradoxical’, and so the appropriate task of constitutional theory is to conceive the appropriate democratic relation between the voluntarist constituent power and the constitutional form that it inaugurates. Though this has become a pivotal instrument for political and legal theorists engaging with constitutionalism, constituent power is cast too constrictively.